Early rebleeding in patients with subarachnoid haemorrhage under intensive blood pressure management. Issue 8 (August 2015) - Oheda, Motoki; Inamasu, Joji; Moriya, Shigeta; Kumai, Tadashi; Kawazoe, Yushi; Nakae, Shunsuke; Kato, Yoko; Hirose, Yuichi
Abstract: The objective of this study was to report the frequency and clinical characteristics of early rebleeding in subarachnoid haemorrhage (SAH) patients who underwent intensive blood pressure (BP) management. Patients with aneurysmal SAH frequently present to the emergency department (ED) with elevated BP. Intensive BP management has been recommended to lower the risk of early rebleeding. However, few studies have reported the frequency of early rebleeding in SAH patients undergoing BP management. In our institution, SAH patients with systolic BP (SBP) > 140 mmHg received continuous intravenous nicardipine to maintain their SBP within 120 ± 20 mmHg after diagnosis. An attempt to implement intensive BP management was made on 309 consecutive SAH patients who presented to our ED within 48 hours of SAH onset. Overall, 24 (7.8%) of the 309 patients sustained early rebleeding. Fifteen patients sustained early rebleeding before the implementation of BP management, and the other nine sustained early rebleeding after the implementation of BP management. Therefore, the frequency of early rebleeding under BP management was 3.1% (9/294). When the 309 patients were dichotomised using ED SBP of 140 mmHg as a cut off (SBP > 140 mmHg; n = 239 versus SBP ⩽ 140 mmHg; n = 70), the latter counter-intuitively exhibited a significantly higher frequency of early rebleeding (5.9% versus 14.2%; p  = 0.04). This relatively low frequency of early rebleeding under BP management may be acceptable. However, early rebleeding is not eradicated even with strict BP control as factors other than elevated BP are involved. ED SBP within the target range (SBP ⩽ 140 mmHg) does not negate the risk of early rebleeding. Other treatment options that reduce the risk should also be explored.